SCIENTIFIC AND THEORETICAL VIEWS ON ENSURING THE ECONOMIC STABILITY OF SERVICE SECTOR ENTITIES. - Shermatova Nargiza Zafar qizi, (World Scientific Research Journal, 2025)
Annotation: The article analyzes the main factors influencing the economic sustainability of service sector entities in modern market conditions. It emphasizes the importance of financial stability, innovation, and digital transformation in maintaining competitiveness. The study identifies challenges faced by service enterprises and suggests ways to enhance their operational efficiency. The role of government regulation and public-private partnerships in ensuring sustainable growth is discussed. Particular attention is paid to resource optimization and human capital development. The research uses comparative and analytical methods to evaluate performance indicators. Empirical data show the necessity of improving management mechanisms and digital infrastructure. The paper highlights the importance of adapting global standards for sustainable development. Recommendations are provided to strengthen the resilience of service enterprises. The results contribute to improving the theoretical and practical basis of economic sustainability.